2020
DOI: 10.1177/1089253220920497
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Organ Transplantation: Noteworthy Literature in 2019

Abstract: In the year 2019, we identified and screened over 400 peer-reviewed publications on pancreatic transplantation, over 200 on intestinal transplantation, and over 1900 on kidney transplantation. The liver transplantation section focuses on and features selected articles among 70 clinical trials published in 2019. This review highlights noteworthy literature pertinent to anesthesiologists and critical care physicians caring for patients undergoing abdominal organ transplantation. We explore a broad range of topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…These studies have found that 24.6% to 33% of donors experience some degree of CPSP for at least 19 months after surgery and identified the presence of pre-operative and acute post-operative pain as risk factors for its development [73,74]. That perioperative pain before or after RT is a risk factor for development for CPSP [73,74] shows the importance of comprehensive analgesic guidelines and standardised practices such as ERAS protocols to ensure patient comfort in the long term [75]. To this end, an ongoing study at the Thomas Jefferson University aims to further address perioperative non-opioid analgesia as an aspect of ERAS protocols in RT.…”
Section: Renal Transplantationmentioning
confidence: 99%
“…These studies have found that 24.6% to 33% of donors experience some degree of CPSP for at least 19 months after surgery and identified the presence of pre-operative and acute post-operative pain as risk factors for its development [73,74]. That perioperative pain before or after RT is a risk factor for development for CPSP [73,74] shows the importance of comprehensive analgesic guidelines and standardised practices such as ERAS protocols to ensure patient comfort in the long term [75]. To this end, an ongoing study at the Thomas Jefferson University aims to further address perioperative non-opioid analgesia as an aspect of ERAS protocols in RT.…”
Section: Renal Transplantationmentioning
confidence: 99%
“…While being the only lifesaving therapy for end‐stage liver disease (ESLD), LT requires a more complex treatment setting over a prolonged time period, as opposed to a single time point surgery, requiring an interdisciplinary approach and high demands on patient compliance. This together with the complexity of the surgical procedure itself and the significant patient morbidity associated with ESLD makes LT a high‐morbidity, expensive, and resource intensive intervention 11–15 …”
Section: Introductionmentioning
confidence: 99%
“…This together with the complexity of the surgical procedure itself and the significant patient morbidity associated with ESLD makes LT a high-morbidity, expensive, and resource intensive intervention. [11][12][13][14][15] The safety and efficacy of individual ERAS measures applied in LT for ESLD were investigated [16][17][18][19][20][21] and initial work demonstrated benefits regarding short-term outcomes and associated costs. 22 Recently, more comprehensive ERAS protocols including multiple aspects of pre-, intra-, and post-operative components were evaluated and the importance of exploring their benefits in a setting of LT for ESLD discussed.…”
mentioning
confidence: 99%